Meeting community ambulation criteria and confidence with walking on discharge from inpatient rehabilitation were positively associated with performance of outdoor community activities 8 weeks after discharge. Issue 22 (23rd October 2022) - Robins, Leslie; Taylor, Nicholas F.; Hogan, Georgia; Callisaya, Michele L.; Sounthakith, Vatthana; Snowdon, Megan; Brooks, Sarah; Scanlon, Sinead; Urmston, Kim; Snowdon, David A.
Abstract: Purpose: To assess whether meeting criteria for community ambulation and ambulatory self-confidence on discharge from inpatient rehabilitation are associated with participation in community activities. Methods: Prospective longitudinal observational study design. Participants were assessed within 48-hours of discharge on ability to complete tasks reflective of community ambulation (walking 315 m, ascending/descending three stairs, a ramp, and a street curb and walking at 0.44 m/s) and ambulatory self-confidence. At 8 weeks post-discharge frequency of participation in domestic, leisure/work and outdoor activities was measured using the Frenchay Activities Index (FAI). Multivariable regression analysis determined factors associated with total and outdoor FAI score. Results: Seventy-four of 79 participants were followed up at 8 weeks post-discharge. Meeting all ambulation criteria was positively associated with FAI outdoor score ( β  = 1.85, 95%CI 0.01–3.69, p  = 0.049). Ambulatory self-confidence was positively associated with FAI outdoor score ( β  = 0.03, 95%CI 0–0.05, p  = 0.032) and FAI total score ( β  = 0.05, 95%CI 0–0.1, p  = 0.040). Age ( β = −0.22, 95%CI −0.36 to −0.08, p  = 0.003) and living alone ( β  = 3.36, 95%CI 0.10–6.61, p  = 0.044) were associated with FAI total score. Conclusions: Capacity to meet ambulation criteria and ambulatory self-confidence are modifiable factors that could be targeted during rehabilitation to improve participation in community activities. Implications for rehabilitation: Meeting community ambulation criteria and confidence with walking on discharge from inpatient rehabilitation are positively associated with performance of outdoor community activities 8 weeks after discharge. Capacity to meet community ambulation criteria and ambulatory confidence may be useful measures for rehabilitation teams to consider when discharging patients home. Meeting ambulation criteria and ambulatory confidence are modifiable factors that could be addressed through targeted therapy to improve community integration following hospitalisation.